The Economic Evaluation of Marketed Surplus, and Factors Affecting It and Marketing Efficiency of Milk and Milk Products in Karnataka, India - Revappa M Rebasiddanavar; Ajay verma; Swati Prakash Relekar (Archives of Current Research International, 2024)
Milk is perishable in nature and its shelf-life is very short in unprocessed form. This must therefore be disposed of or converted as soon as possible into different milk products. Two major districts in Karnataka namely, Mandya and Dharwad were selected purposively for the purposed study. From each selected block, one village was selected in random fashion. Twenty-five milk producer households were sampled in each of the selected villages to collect the desired information. Various techniques like marketed surplus and regression analysis were used for analyzing the data. Marketed surplus is quantity of produce brought to the market for sale. Therefore, farmers of various herd size categories need to identify the contribution and the maximum share in the marketed surplus of milk. For the present study, consideration was given to the number of milk animal assets, family size, land holding, milk production per day, milk price and net return obtained from milk production among various factors influencing the marketed milk surplus. Overall marketed surplus of milk was highest for large herd size category households (84.15 per cent) followed by medium (82.63 per cent) and small category households (80.76 per cent). Producer’s share in consumer’s rupee was observed 100 per cent in case of direct channel because no milk marketing agencies were present in this channel. The value of the coefficient of multiple determination ( was 0.722 which means only 72.20 per cent of the total variation in marketed surplus of milk was explained by the variables included in the regression model. Due to increase in family size, the family consumption requirement of milk increases which negatively affects the marketed surplus of milk. Encouraging knowledge sharing among farmers could help improve overall dairy management. These measures could help maximize the marketed surplus of milk and stabilize the dairy market.